The university of Alberta library : - Distad, N. Merrill (University of Alberta Libraries, 2009)
The University of Alberta Library is now the second largest in Canada and one of the top twenty academic research libraries in North America. Over the past one hundred years it has gone through reconstruction and moves, additions of new wings and branch libraries, regularly expanding collections, and at times, tight budgetary considerations. The author, Merrill Distad (research & special collections services, University of Alberta Library) comprehensively covers the changes. (Book News Inc)